The doctors of the Warsaw Ghetto - Ciesielska, Maria, 1971- (Holocaust (Boston, Mass.), 2022)
"Based on years of archival research, "The Doctors of the Warsaw Ghetto" is the most detailed study ever undertaken into the fate of more than 800 Jewish doctors who devoted themselves, in many cases until the day they died, to the care of the sick and the dying in the Ghetto. The functioning of the Ghetto hospitals, clinics and laboratories is explained in fascinating detail. Readers will learn about the ground-breaking research undertaken in the Ghetto as well as about the underground medical university that prepared hundreds of students for a career in medicine; a career that, in most cases, was to be cut brutally short within weeks of them completing their first year of studies"--